A user study of the family history center at the church of Jesus Christ of latter-day saints Manila Philippines administration office - Quiñones, Klarenz Kristoffer M. (School of Library and Information Studies, University of the Philippines Diliman, 2017)
Archives aim to preserve documents for easy access of the users. Satisfying the information needs of a user is a top priority of archives. In this light, an archives user study was conducted at the Family History Center (FHC) of The Church of Jesus Christ of Latter-Day Saints (LDS) Manila Philippines Administration Office. This study aims to profile FHC users and evaluate the FHC archives in terms of service product and process, service environment, service workers, and other yardsticks to improve and develop the archives to better serve FHC users. Data gathering for this research was done through an online survey of FHC users and through a semi-structured interview with the FHC's Manila Administration Office Director